Combining Ability and Heterosis for Grain Yield and Rust Resistance in Pearl Millet - Lubadde, G.; Tongoona, P.; Derera, J.; Sibiya, J. (Journal of Agricultural Science, 2016)
Pearl millet is a dual-purpose crop in semi-arid zones of Uganda. However, no studies have been conducted to determine the gene effects for yield and yield-related traits and rust resistance in these environments; yet this knowledge is important in improving grain yield and rust resistance. A North Carolina II mating design was adopted to study the genetic effects for rust resistance and yield-related traits of improved pearl millet genotypes. The experimental design to study the objectives was alpha in two [locations, seasons and replications]. A higher proportion of general combining ability (GCA) effect was observed for grain yield, days to 50% flowering, days to 50% anthesis, flower-anthesis interval, days to 50% physiological maturity, plant height, total tiller number, number of productive tillers, percentage of productive tillers, panicle area, leaf area, 1000-grain weight, biological yield and harvest index. The specific combining ability (SCA) effect was predominant for area under disease progress curve. Eleven hybrids performed better than the best male parent and five crosses performed better than the best female parent for grain yield while all the fifteen selected best crosses performed better than all parents for area under disease progress curve. Ten crosses were more resistant to rust than the best male parent and all the crosses were more resistant to rust than the female parents. The additive gene action was predominant for grain yield, rust severity at 50% physiological maturity, days to 50% flowering, days to 50% anthesis, total tiller number, percentage of productive tillers, panicle area, 1000-grain weight, biological yield, harvest index and leaf area. High better-parent heterosis was also observed for most traits including grain yield and rust resistance. The traits were also characterized by relatively low levels of narrow sense heritability.
Keywords: Combining ability; Gene action; Heritability; Heterosis; Rust